THE EFFECT OF POLLARD REPLACEMENT WITH RICE BRAN SUPPLEMENTED MULTIVITAMIN-MINERAL IN RATION ON THE PERFORMANCE CROSSBRED PIG - G. E., Stradivari; Partama, I. B. G.; Bidura, I G. N. G. (Majalah Ilmiah Peternakan; Vol 22 No 2 (2019): Vol. 22 No.2 (2019)DO - 10.24843/MIP.2019.v22.i02.p03, 2019)
The purpose of this study is to determine the effect of pollard replacement with rice bran supplemented multivitamin-mineral in ration on the performance of crossbred pigs. The design used a randomized block design (RBD) consists of 3 treatments and 4 groups as replications. The treatments A (control): pollard in ration without multivitamin-mineral supplementation, B: ration with rice bran without multivitamin-mineral supplementation, C: ration with rice bran which supplemented with 0.20% multivitamin-mineral. The variables observed were final body weight, weight gain, feed consumption, FCR, protein, crude fiber, and fat consumption.The results showed that the ration with rice bran supplemented with 0,20% multivitamin-mineral were able to produce the same final weight, weight gain, and FCR with the control and increase significantly crude fiber consumption 45,57 g/h, 85,63 g/h of fat consumption, and decrease 207,64 g/h protein consumption. However, the feed consumption showed no significant differences in each treatment. It can be concluded that pollard replacement with rice bran supplemented with 0,20% multivitamin-mineral in ration fed to crossbred pigs can produce similar production performance as control, and increase consumption of crude fiber, and fat consumption.